2018
DOI: 10.1016/j.lwt.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different frequencies of ultrasound on the activity of horseradish peroxidase

Abstract: Please cite this article as: Tsikrika, K., Chu, B.-S., Bremner, D.H., Lemos, M.Adí., The effect of different frequencies of ultrasound on the activity of horseradish peroxidase, Abstract 6Ultrasound technology has been studied by food researchers as an alternative 7 method for thermal processing. The use of ultrasound as a way to inactivate and/or 8 activate enzymes has been widely studied at low frequencies (20-40 kHz), however, 9 little research on the effect of high frequencies has been reported. Thus, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Free radical-mediated deactivation mechanisms and cleavage of the functional groups from enzymes could occur during US treatment and is the likely reason for the modifications in proteins and enzymes. For example, the inactivation of peroxidase as a result of haem group dissociation and the loss of iron was facilitated by hydroxyl radicals from US cavitation [ 69 ].…”
Section: Application Of Us In Herbal Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…Free radical-mediated deactivation mechanisms and cleavage of the functional groups from enzymes could occur during US treatment and is the likely reason for the modifications in proteins and enzymes. For example, the inactivation of peroxidase as a result of haem group dissociation and the loss of iron was facilitated by hydroxyl radicals from US cavitation [ 69 ].…”
Section: Application Of Us In Herbal Sciencementioning
confidence: 99%
“…The position of the disulfide motif in the center of the macromolecular framework (e.g. Hydrocarbon) enabled the efficient mechanochemical scission and the release of this monoterpene molecule [ 69 ]. A US mechanophore breakage (mechanochemically breakage of the polymer reactive units like cyclic rings) can occur in extracts solutions via the shear stress caused by the collapse of US-induced cavitation bubbles [ [73] , [74] ].…”
Section: Application Of Us In Herbal Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…e inactivation of horseradish peroxidase was investigated by Tsikrika et al [98] who determined that sonication for 60 min using 20, 378, 583, 862, 995, 1144, and 1175 Hz ultrasound at power levels (acoustic energy) between 2.1 and 64 W was very effective at inactivating the enzymes with little effect observed at the 20 kHz lower frequency. e fact that the greatest levels of inactivation were observed at 378 and 583 nm suggests that some radical effect may be the cause.…”
Section: Chemical Food Safetymentioning
confidence: 99%
“…Moreover, it needs to be considered that during acoustic cavitation the extremely high local temperature, pressure, and shearing forces – attributable to the collapse of cavitation bubbles and the generation of high-velocity microjets – can also affect both the enzyme molecule and the solid substrate, modifying their chemical and physical properties. Previous studies have shown that intensive ultrasonication can change the protein molecules, resulting in a decrease in the activity of enzymes [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%